Estudio de Factibilidad para la Implementación de un Centro de Masaje de Relajación Antiestrés, para el Cantón Catamayo, Provincia de Loja. - Cumbicus Paute, Darwin Ramiro (2016)
The present thesis was carried out it according to the general objective: To "elaborate a study of feasibility for the implementation of a center of massage of relaxation antiestres, for the canton Catamayo, county of Loja." Which was completed according to the specific outlined objectives. For that which a market study that allowed to determine the demand of the service, settled down it offers, use per capita, demands unsatisfied and the market plan with the purpose of defining which our market will be it puts, as well as the number of times that you/they will make use of the service. The size of the company the same one was determined that he will offer 14.496 services per year, and their installed capacity will cover 5,83% of its unsatisfied demand, for the first year of lifespan 80% of the installed capacity, the localization of the company was used it will be in the canton Catamayo, which was determined by means of the elaboration of the ponderación womb by points, being based on the most outstanding factors for the implementation. Then he thinks about an organizational study here the legal and administrative base it is determined, for the good operation it is designed a structural, functional flowchart and manual of functions and it proposes the philosophy and values so that the collaborators know which is the end that looks for the company for their clients. For the implementation of the Center of Massage of Relaxation Antiestres an investment of $27.113,30 is needed; whose financing will be covered in its entirety by the partners; you prevé to obtain for the first year of lifespan revenues for an I mount of $137.570,26 and expenditures of $ 120.879,63; by means of the financial evaluation, after having analyzed the different indicators a Net positive Current Value of $50.866,06 it was determined; the Internal Rate of Return will be of 70,24%, the Relationship between the Benefit and Cost was of $ 1,20, as well as the invested capital will be recovered in a 2 year-old lapse 4 months and 12 days, the analysis of sensibility indicates that the company will support an increment in the costs of 9,01% and decrease in the revenues of 7,51%. By means of the results obtained in the project based on the carried out studies you concludes that if feasibility exists for the implementation of the Center of Massage of Relaxation Antiestrés in the canton Catamayo, reason why it is recommended that it is executed since it is profitable and he/she helped to the growth of the economy of the canton.